A novel colonoscopy reporting system enabling quality assurance - van Doorn, Sascha C.; van Vliet, Joost; Fockens, Paul; Dekker, Evelien (Endoscopy, 2014)
Background and study aims: The quality of colonoscopy can only be measured if colonoscopy reports include all key quality indicators. In daily practice, reporting is often incomplete and not standardized. This study describes a novel, structured colonoscopy reporting system, which aims to generate standardized and complete reports and to facilitate the automatic analysis of colonoscopy quality indicators. Methods: A new colonoscopy reporting system (EndoALPHA) was developed. The system reports all colonoscopy quality indicators, as well as pathological findings, in a systematic manner using structured terminology. All essential items carry specific codes, which enables statistical analysis and the automatic generation of reports of all quality indicators. The EndoALPHA reporting system was tested with regard to completeness of reporting and evaluation of quality indicators both for individual endoscopists and the endoscopy unit. Results: In 2012, all 810 colonoscopies performed at one colonoscopy center were documented using EndoALPHA. Overall, 94 % of performed colonoscopies were reported completely using the encoded terminology. Individual unadjusted cecal intubation rates were above 90 % for all endoscopists (mean 96.7 %), and the adenoma detection rate was above 20 % for all endoscopists (35.4 % for the unit). Conclusion: The novel EndoALPHA reporting system enables automatic quality assessment on two levels: the completeness of reporting can be evaluated, and if this is adequate, the quality of the colonoscopies can also be assessed. Integrated with feedback, benchmarking and training, the reporting system may facilitate quality improvement for colonoscopy services.